Laporan Kasus: Pengobatan Fisioterapi pada Kasus Bahu Beku untuk Meningkatkan Ruang Lingkup Gerak Sendi dan Kemampuan Aktivitas Sehari-hari - Hargiani, Fransisca Xaveria; Sartoyo, Sartoyo (NUCLEUS, 2023)
Frozen shoulder is a very common condition in clinical practice, affecting 2–5% of  the general population. Frozen shoulder (FS) rarely occurs before  age  40  and typically affects ages 50 to 70. Women are more commonly affected  than men. Frozen shoulder is classified into primary and secondary, where primary frozen shoulder is due to the presence of attachments around the joint capsule and secondary frozen shoulder is due to sprains, strains, tendinopathy, tendon tear or bursitis. This study, conducted at Mutiara Sukma Mental Hospital NTB in September-October 2022, aimed to evaluate the effectiveness of physiotherapy interventions on a 64-year-old patient with frozen shoulder, mental disorders, and diabetes, using a case study approach. Interventions included Infrared therapy and TENS (Transcutaneous Electrical Nerve Stimulation) for pain reduction and muscle relaxation, as well as Neuromuscular Taping (NMT) for enhanced lymphatic drainage and pain relief. Assisted active movements and free active movements were also applied to maintain and improve joint range of motion and muscle strength. The results showed significant improvements in pain reduction and increased range of motion and shoulder function, with pain evaluation using the Numerical Rating Scale (NRS) and Shoulder Pain and Disability Index (SPADI) indicating positive progress during therapy sessions. This underscores the benefits of combined physiotherapy interventions in treating frozen shoulder, especially in patients with comorbid mental disorders.